(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The present paper examines the cost efficiency of commercial banks byusing a non-parametric Data Envelopment Analysis Technique. The cost efficiencymeasures of banks are examined under both separate and common frontiers. Thispaper also empirically examines the impact of mergers on the cost efficiency ofbanks that have been merged during post liberalization period. Banks play an important role in the economic development of a state.The banks play the role of financial intermediaries in the economic developmentof a state. The commercial banks help in flow of investment capital throughoutthe market place. The main tool for resource allocation in the economy iscredit disbursed by the banks. When we look at the performance of the banks andalso the services provided to the larger societies, we often find a glaringbias of public sector (PS) banks only for the urban areas. But Odisha has apopulation of 4.20 crore, of which 3.50 crore (83.33%) live in (51313) villages(as per 2011 census). Out of 51313 villages of Odisha, commercial banksfunction only in 1724 villages. The banking system in Odisha consists of publicsector banks, private banks, development banks, specialized banks, andcooperative banks. Are the banks, operating Odisha, doing justice? Can the state bank onthose banks for the socio-economic development of the masses? Against thisbackground, authors have analysed the operational statistics of all the banksoperating in Odisha, to make a comparative study of their role as well as theperformance parameters of Regional Rural Banks (RRBs) and other PS banks. Through this article an attempt has been made to assess whether thecommercial banks functioning in Odisha have properly discharged theirresponsibilities towards the economic development of the state, especiallyrural Odisha (India).